Black Ginseng Extract Prevents Neuroinflammation and Enhances Learning Behavior in Mice - Saba, Evelyn; Lee, Yuan Yee; Kim, Minki; Kim, Seung-Hyung; Choi, Sung Keun; Jeon, Byeong Seon; Rhee, Man Hee (Pakistan Journal of Nutrition, 2018)
Background and Objective: Ginseng is widely used in the Korean peninsula as a traditional herbal treatment for numerous ailments in the body, like inflammation, tumors and cardiovascular diseases. Therefore the prime objective of the present study was to investigate the effects of ginseng on neuro-inflammation in vitro and in vivo. Methodology: In the present study, two types of ginseng extracts, Red Ginseng (RG) and black ginseng ethanol extract [BG (etoh)] was used and their efficacy in the Morris water maze test for spatial learning behavior and their anti-inflammatory effects in BV2 microglial cells was evaluated. Results: Present study showed that both extracts, particularly BG (etoh), improved learning behavior in scopolamine-impaired mice in water maze tests. Moreover, these extracts also inhibited nitric oxide production in BV2 microglial cells, with significant suppression of proinflammatory cytokines, especially iNOS, COX-2 and IL-1β. The protein expression of MAPK and NF-κB pathway factors was also diminished by these extracts, indicating that they not only improve memory impairment, but are also potent anti-inflammatory agents for neuroinflammatory diseases. Conclusion: It is concluded that BG (etoh) extract is more effective in preventing neuroinflammation and enhancing learning behavior as compared red ginseng extract.